PENGARUH LATIHAN LOMPAT TALI DENGAN PERLAHAN TERHADAP DAYA TAHAN PADA ATLET TENIS MEJA PUTRA CLUB PTM MANDIRI PANDAU - Dwy Saputra; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem addressed in this research is the lack of endurance of athletes when playing long games, the lack of good long rally games to reverse the opponent's blow when the game is long, when competitive athletes are not optimal at returning the opponents. clap when entering the final sets. This research aims to determine the effect of slow skipping rope on endurance. The format of this research is (using a single group pretest-posttest design approach) with. The data in this research was the entire population of 6 subjects. The instrument used in this research is the use of a multi-stage fitness test that aims to determine the durability of the sample. Thereafter, the data was statistically processed to test for normality using the Lilifours test at a significant level of 0.05α. Based on statistical data analysis, the data is normally distributed. Based on the t-distribution test, which is 6,600 > 2,016 Tcount > Ttable data, it means there is an effect of slow skipping rope on endurance in male table tennis athletes at PTM Mandiri Pandau club.Key Words: Slow Jump Rope Exercise, Endurance, Table Tennis